Comparison of the Effect of Paddle Resisted Training with Fin Assisted Training on 50 M Freestyle Swimming Speed - Dirgantara, Erlangga; Kardjono, Kardjono; Pitriani, Pipit (MEDIKORA, 2026)
In the sport of swimming speed is a benchmark when athletes compete. To increase speed, arm and leg muscle strength is required. Lack of power in the leg kick and arm stroke phase will reduce swimming speed. This study aims to determine the difference in the effect of Paddle Resisted Training with Fin Assisted Training on 50 m freestyle swimming speed. The method used in this research is experimental method. The population used in this study were all members of the AKKSA Swimming Club. The sample amounted to 10 people who were taken using purposive sampling technique. The instrument in this study used the 50m Freestyle Swimming Test. The data analysis technique used is the Paired Sample t-test and the Independent Sample t-test. The results of this study indicate that there is a significant effect of Paddle Resisted Training with Fin Assisted Training on 50 m freestyle swimming speed and there is no significant difference in effect between Paddle Resisted Training and Fin Assisted Training on 50 m freestyle swimming speed.